Rancangan Pembelajaran Digital Berbasis Inovasi Teknologi - Sri Hartati; Sulistya Utami; Nadiya Halimah; Isti Sufina; Mar’atus Sholihah (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2025)
The transformation of education in the digital era demands a learning design that is not only adaptive but also innovative and aligned with technological advancements. This paper aims to examine the characteristics of effective digital learning design, explore innovative technologies that can be integrated, and identify presentation strategies that ensure optimal understanding and implementation. The method used is a descriptive-analytical literature review, drawing from recent publications in digital education and educational technology. Effective digital learning is characterized by flexibility, interactivity, personalization, and the support of adaptive technologies such as Learning Management Systems (LMS), Artificial Intelligence (AI), and interactive multimedia. Furthermore, technologies such as Augmented Reality (AR), Virtual Reality (VR), and gamification enhance the learning experience by making it more contextual and engaging. To ensure successful implementation, the presentation of digital learning design must be systematic, communicative, and user-centered. The use of visual media, live demonstrations, supplementary materials, and continuous training are essential elements of an effective presentation strategy. The findings of this study are expected to serve as a reference for educators, curriculum developers, and policymakers in designing and implementing transformative digital learning aligned with the demands of the 21st century.